(untitled) - Epstein, Richard J. (New York, 2003)
This book is a fresh view of clinical medicine designed to meet the specific needs of candidates preparing for examinations. The author outlines a streamlined approach to revision, consisting both of strategies for dealing with clinical problems and of essential information relating to topical issues.
Keywords: Y học,Internal medicine,Medicine,Nội khoa; Examinations, questions, etc.,Thi, các câu hỏi, vv